Spoon Stabilization for Essential Tremor Patients Using PID Control Optimized by PSO - Zartika, Putri Ayu; Muslim, Muhammad Aziz; Yudaningtyas, Erni (Kinetik: Game Technology, Information System, Computer Network, Computing, Electronics, and Control, 2025)
Essential tremor is a neurological disorder that causes uncontrollable hand tremors, interfering with daily activities such as eating. This study aims to develop a spoon stabilization system controlled by a Proportional-Integral-Derivative (PID) controller, which was tuned using Particle Swarm Optimization (PSO) and the Cohen-Coon method for performance comparison. The system utilized an inertial measurement unit to detect tremors, while a Kalman filter was used to reduce noise before a microcontroller controlled a servo motor to stabilize the spoon. The system was evaluated through simulations and hardware implementation, and its performance was assessed based on rise time, overshoot, delay time, and settling time. The results showed that the Kalman filter significantly reduced noise, lowering the average pitch angle error deviation from 1.028° to 0.037° and the roll angle error from 0.822° to 0.031°. The PSO-based tuning outperformed the Cohen-Coon method in response speed and system stability, achieving a faster rise time (0.09 s for roll, 0.34 s for pitch), a shorter settling time (0.74 s for roll, 0.59 s for pitch), and a lower delay time (0.1 s for roll, 0.15 s for pitch). However, the Cohen-Coon method resulted in a lower overshoot for the roll angle (6.08%) compared to the PSO-based tuning (11.98%). The findings suggest that implementing a PID controller optimized via PSO is a viable approach for spoon stabilization in individuals with essential tremor.